Singing class. - United States. Army. Signal Corps (photographer):::Creator::::::::::::; Flaherty, John Melvin (collector):::Contributor::::::::::::
Photograph shows an evacuee teacher leading a singing class at Portland, Oregon Assembly Center. The Portland Assembly Center was formerly known as the North Portland International Livestock Exposition Center.